2022
DOI: 10.1002/hep.32449
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota–derived short‐chain fatty acids regulate group 3 innate lymphoid cells in HCC

Abstract: Background and Aims: Type 3 innate lymphoid cells (ILC3s) are essential for host defense against infection and tissue homeostasis. However, their role in the development of HCC has not been adequately confirmed. In this study, we investigated the immunomodulatory role of short-chain fatty acids (SCFAs) derived from intestinal microbiota in ILC3 regulation.Approach and Results: We report that Lactobacillus reuteri was markedly reduced in the gut microbiota of mice with HCC, accompanied by decreased SCFA levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 34 publications
0
62
0
Order By: Relevance
“…IL-17A was reported to induce tumor angiogenesis ( 87 , 88 ). Consistently, HCC mice displayed a robust increase in IL-17A expression in hepatic type 3 innate lymphoid cells (ILC3s) ( 58 ). Moreover, tumor-infiltrating ILC3s were a poor prognosis factor in HCC patients.…”
Section: The Gut Microbiota and Innate Immunitymentioning
confidence: 90%
See 1 more Smart Citation
“…IL-17A was reported to induce tumor angiogenesis ( 87 , 88 ). Consistently, HCC mice displayed a robust increase in IL-17A expression in hepatic type 3 innate lymphoid cells (ILC3s) ( 58 ). Moreover, tumor-infiltrating ILC3s were a poor prognosis factor in HCC patients.…”
Section: The Gut Microbiota and Innate Immunitymentioning
confidence: 90%
“…It is not surprising that the gut microbiota regulates the development of liver cancer. The relative abundance of Lactobacillus reuteri was decreased in hepatocellular carcinoma (HCC)-bearing mice compared with control mice ( 58 ). HCC mice displayed a substantial reduction in the serum concentration of microbial metabolites including acetate and valerate.…”
Section: The Gut Microbiota and Innate Immunitymentioning
confidence: 99%
“…Moreover, it has been found that the SCFAs pentanoate can reduce IL-17A production in CD4 + T cells by inhibiting histone deacetylase activity ( 55 ). Similarly, probiotics that synthesize SCFA, particularly acetate, are involved in reducing IL-17A in hepatic type 3 innate lymphoid cells (ILC3s) ( 56 ). It was also found that dietary intake of RS and decreased colonic IL-17A stimulate intestinal immune and endocrine responses that may alter liver health ( 48 ).…”
Section: Potential Mechanisms Of Resistant Starches On Regulating The...mentioning
confidence: 99%
“…[7] Hu et al found that a pronounced reduction of L. reuteri was observed in carcinogen-induced primary HCC-bearing mice, whereas intestinal transplantation of L. reuteri exhibited significant antitumor immune response to curb HCC progression. [5] L. reuteri used a variety of monosaccharides and disaccharides to produce sodium acetate in a 6-phosphogluconate/ phosphoketolase pathway-dependent manner. [8] Hu et al suggested that intestinal L. reuteri-inhibited HCC progression was due to its metabolite sodium acetate, thus determining the mechanism in details.…”
mentioning
confidence: 99%
“…Hu et al found that, after transplantation with gut microbiota from healthy mice or Lactobacillus reuteri (L. reuteri) to the carcinogen-induced primary HCC-bearing mice, the proportion of IL-17A + ILC3s in the liver was evidently decreased, leading to the reduced IL-17A production and suppressed HCC development, thus suggesting the tumor-promotive roles of hepatic ILC3s. [5] IL-17A is known to induce the secretion of chemokine (C-X-C motif) ligand 5 (CXCL5) by HCC cells and then recruit the infiltration of bone marrow-derived suppressor cells (MDSCs) through CXCL5/cysteine-X-cysteine receptor 2 axis, thus promoting MDSC activation, exacerbating tumor immunosuppression, and favoring HCC development. [4] Moreover, the findings by Hu et al also reveal that IL-17A-producing ILC3s can promote HSC activation and fibrosis progression.…”
mentioning
confidence: 99%